(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2015)
In this paper, we examine the steady natural convection boundary layer flow of an incompressible viscous nanofluid along an inclined plate at an angle α in a porous medium. The model used for the nanofluid includes the effects of Brownian motion and thermophoresis, while the Darcy model is used for describe the porous medium. The resulting similarity equations are solved numerically using finite difference method via bvp4c routine. Many results are obtained and representative set is displayed graphically to illustrate the influence of the various parameters on different profiles. The conclusion is drawn that the flow field, temperature and nanoparticle volume fraction shapes are significantly influenced by nanofluid Lewis number, Brownian motion parameter and thermophoresis parameter.